MAS' Challenges In The 21st Century - Fern, Ng Huay (2001)
This paper traces the history of MAS, the internal and external environments in which it operates, its strengths, weaknesses, opportunities and threats and finally the strategies it employ in its core competencies to reposition itself in the aviation industry. The strategies adopted by MAS' management preceding the financial crisis and how it expects to recapture the confidence of the shareholders and the direction of the MAS in the future.